Untargeted and Targeted Metabolomics Reveal the Underlying Mechanism of Aspirin Eugenol Ester Ameliorating Rat Hyperlipidemia via Inhibiting FXR to Induce CYP7A1 - Xiao-Rong, Lu; Ning, Ma; Xi-Wang, Liu; Shi-Hong, Li; Zhe, Qin; Li-Xia, Bai; Ya-Jun, Yang; Jian-Yong, Li (Frontiers in Pharmacology, 2021)
Hyperlipidemia is an important lipid disorder and a risk factor for health. Aspirin eugenol ester (AEE) is a novel synthetic compound which is made up of two chemical structural units from aspirin and eugenol. Therapeutic effect of AEE on hyperlipidemia has been confirmed in animal model. But the action mechanism of AEE on hyperlipidemia is still poorly understood. In this study, we investigated the effects of AEE on liver and feces metabolic profile through UPLC-Q-TOF/MS-based untargeted metabolomics in hyperlipidemia hamster induced with high fat diet (HFD), and the effects of AEE on the expression of genes and proteins related to cholesterol and bile acids (BAs) in HFD-induced hyperlipidemia SD rat. The concentrations of 28 bile acids (BAs) in the liver from hyperlipidemia SD rat were also quantified with the application of BAs targeted metabolomics. The results of untargeted metabolomics showed that the underlying mechanism of AEE on hyperlipidemia were mainly associated with amino acid metabolism, glutathione metabolism, energy metabolism, BAs metabolism and glycerophospholipid metabolism. AEE induced the expression of the BA-synthetic enzymes cholesterol 7α-hydroxylase (CYP7A1) by the inhibitation of BA nuclear receptor farnesoid X receptor (FXR) in liver, which resulted in accelerating the conversion of cholesterol into bile acids and excrete in feces. The results of BAs targeted metabolomics showed that AEE elevated the glycine-conjugated BAs level and decreased the tauro-conjugated BAs level. In conclusion, this study found that AEE decreased FXR and increased CYP7A1 in the liver, which might be the possible molecular mechanisms and targets of AEE for anti-hyperlipidemia therapies.